Advance in nanocomposites based on hybrid organo-silicate matrix - Kudryavtsev, Pavel; Figovsky, Oleg; Kudryavtsev, Nikolai (Publishing House of Lviv Polytechnic National University, 2016)
This paper presents some features and applications of sol-gel technology for production of organic mineral hybrid nanocomposites which might be affected. It defines some principles of synthesis and application of hybrid nanomaterials in various fields of technology, using specific examples. Наведено функції і можливості золь-гель технології для виробництва органічних мінеральних гібридних нанокомпозитів, на які можна впливати. На конкретних прикладах показано вплив на деякі принципи синтезу і застосування гібридних наноматеріалів у різних областях техніки.
Поступ в нанокомпозитах на основі гібридної органо-силікатної матриці
Keywords: nanocomposites; nanotechnology; sol-gel; hybrid composites; silicate matrix; нанокомпозит; нанотехнологія; золь-гель; гібридні композити; силікатна матриця